The environs of the massive runaway star BD+43 3654 - Peri, Cintia Soledad (2010)
The very massive runaway star BD+43° 3654 (O4 If) seems to be related with a bow shock detected by the MSX mission, that would be the result of the interaction of the strong stellar wind with the ambient matter. Shock-accelerated electrons will cool through synchrotron radiation producing a non-thermal radio source, yet never detected in such scenario. While new Very Large Array observations are carried out, we have examined archive data and present here the findings.